Novel tetrakis–phthalocyanines bearing pyrimidine derivative: crystal XRD analysis, enzyme inhibition, molecular docking, and anticancer effects. Issue 1 (2nd January 2023) - Günsel, Armağan; Yazar, Bilge; Taslimi, Parham; Erden, Yavuz; Taskin-Tok, Tugba; Pişkin, Hasan; Bilgiçli, Ahmet T.; Yarasir, M. Nilüfer; Gülçin, İlhami
Abstract: In this study, the novel 4-(4-Aminopyrimidin-2-ylthio) phthalonitrile (1) as starting material was synthesized and its 3D structure was verified by the single crystal X-ray diffraction experiment. Then, its peripherally tetra-substituted phthalocyanines (2, 3) and the methylated derivatives (2a, 3a) containing pyrimidine derivative were synthesized. All these newly synthesized compounds were characterized with various spectroscopic methods such as UV–Vis, FT-IR, 1 H-NMR, 13 C-NMR and MALDI-TOF MS by obtaining satisfactory results. In addition, these novel phthalocyanines effectively inhibited acetylcholinesterase enzyme, with K i values in the range of 10.43 ± 2.38 to 41.70 ± 9.32 µM. For the related enzyme, the IC50 values were obtained in the range of 11.68 to 44.28 µM. For α-glycosidase enzyme the most effective K i values of (3a) and (2) were with K i values of 92.87 ± 10.70 and 95.18 ± 17.83 µM, respectively. Indeed, the most potent phthalocyanines against both enzymes were recorded for the purpose of investigating interaction modes of these complexes in the active site of the target enzyme. The cytotoxicity potential of these phthalocyanines against human breast, colon, and prostate cancers demonstrated that these compounds had normal cytotoxic effects. Communicated by Ramaswamy H. Sarma